The feminization of the cooperative bank’s board as a factor differentiating its financial performance - Rafał Balina; Marta Idasz-Balina (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2018)
The research was aimed at showing the relationship between the gender of the CEO and the efficiency of the Polish cooperative banks. The research covered 354 banks operating in Poland in 2013-2015. Based on the conducted research, it has been shown that, for the surveyed Polish cooperative banks, women served as CEOs in significantly smaller banks than men, as the number of clients, the number of members, the total value of assets and the value of equity in male-dominated banks was on average more than double. In banks managed by women. At the same time, the results of the research clearly showed that the gender of the person acting as the chairman of the management board in a cooperative bank had an impact on the level of its financial effectiveness.